Methods to drive systems biology forward - Polychronidou, Maria (Mol Syst Biol, 2017)
The development of new methodologies has driven the expansion of systems biology over the past decades. Technological breakthroughs in sequencing, in quantitative proteomics, in single‐cell measurements, to name only a few, have each opened up whole new fields of research. To highlight the importance of new experimental and computational methodologies in enabling novel biological discoveries, we are pleased to announce the introduction of a new Methods section in Molecular Systems Biology (http://msb.embopress.org/authorguide#methodsguide).